Nanoscale Irregularity Analysis of Carbon Fibre Surfaces with a High-Resolution α-Plot - K. Fukasawa; T. Ohba; H. Kanoh; T. Toyoda; K. Kaneko (Adsorption Science & Technology)
Exfoliated carbon fibres (ECFs) were prepared from preheated mesophase pitch-based carbon fibre by electrochemical treatment. The nitrogen adsorption isotherms on ECFs were measured at 77 K. All the nitrogen adsorption isotherms were transformed into α S -plots using the standard adsorption isotherms for carbon blacks of different crystallinities and the GCMC simulation isotherm. Using the standard isotherm of well-crystallized carbon black, the α S -plot for the ECF prepared from carbon fibre preheated at 3273 K was almost linear, while α S -plots obtained using the standard isotherm of well-crystallized carbon black and the simulated form had have a downward and an upward deviation, respectively. The α S -plots of carbon samples having similar nanoscale crystallite sizes were close to each other, showing that α S -plot analysis was effective for determining the average surface irregularity structure in the nanoscale range.